Multi-subject simulation system - TORIGOE TAKATOMO; YOSHIOKA AKIRA (2022)
The multi-subject simulation system simulates an object world in which a plurality of interacting subjects exist. A multi-subject simulation system is provided with a plurality of subject simulators that simulate each of a plurality of subjects, and a central controller that communicates with the plurality of subject simulators. The operating modes of the central controller include a first mode in which message filtering is not performed and a second mode in which message filtering is performed. When the number of messages received per unit time by the central controller is equal to or less than a threshold value, the first mode is selected. When the number of messages received per unit time by the central controller exceeds a threshold value, the second mode is selected. As a result, it is possible to flexibly use the multi-subject simulation from the viewpoint of suppressing traffic and processing load. 多主体模拟系统进行对象世界的模拟，对象世界中存在相互作用的多个主体。多主体模拟系统具备多个主体模拟器和中央控制器，多个主体模拟器进行多个主体各自的模拟，中央控制器与多个主体模拟器进行通信。中央控制器的工作模式包